From Spreadsheets to Script: Experiences From Converting a Scottish Cardiovascular Disease Policy Model into R - Xin, Yiqiao; Robles‑Zurita, José Antonio; Haghpanahan, Houra; Heggie, Robert; Kohli‑Lynch, Ciaran; Briggs, Andrew; McAllister, David A.; Lawson, Kenny D.; Lewsey, Jim; Gray, Ewan (Springer Nature, 2021)
Given the advantages in transparency, reproducibility, adaptability and computational efficiency in R, there is a growing interest in converting existing spreadsheet-based models into an R script for model re-use and upskilling training among health economic modellers. The objective of this exercise was to convert the Scottish Cardiovascular Disease (CVD) Policy Model from Excel to R and discuss the lessons learnt throughout this process. The CVD model is a competing risk state transition cohort model. Four health economists, with varied experience of R, attempted to replicate an identical model structure in R based on the model in Excel and reproduce the intermediate and final results. Replications varied in their use of specialist health economics packages in addition to standard data management packages. Two versions of the CVD model were created in R along with a Shiny app. Version 1 was developed without health economics specialist packages and produced identical results to the Excel version. Version 2 used the heemod package and did not achieve the same results, possibly due to the non-standard elements of the model and limited time to adapt the functions. The R model requires less than half the computational time than the Excel model. Conversion of the spreadsheet models to script models is feasible for health economists. A step-by-step guide for the conversion process is provided and modellers’ experience is discussed. Coding without specialist packages allows full flexibility, while specialist packages may add convenience if the model structure is suitable. Whichever approach is taken, transparency and replicability remain the key criteria in model programming. Model conversions must maintain standards in these areas regardless of the choice of software.
Keywords: Sistema cardiovascular - Enfermedades - Aspectos económicos; Cardiovascular Disease Policy Model; coding; Economic evaluation